High unprotective anti-HBs antibodies level among vaccinated students in a tertiary teaching hospital in north-eastern Malaysia - Hassan, Murnihayati; Mohamed, Zeehaida; Ismail, Nabilah; Hasan, Habsah; Deris, Zakuan Zainy (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: Universal hepatitis B vaccination to all newborns have been implemented in Malaysia, since 1989, with nationwide coverage of 96.26%. In this study, we aimed to assess the prevalence of anti-HBs and HBsAg among selected undergraduate students who presumably had completed hepatitis B vaccination during their early childhoods. Methods: Results of hepatitis B screening were obtained retrospectively from 239 newly enrolled undergraduate students at Health Campus, UniversitiSains Malaysia, in 2018. Serum samples were previously tested for the presence of anti-HBs and HBsAg using chemiluminescence immunoassay. Epidemiological data, anti-HBs and HBsAg were analysed using a descriptive statistical method. Results: Anti-HBs was undetected in 82.2 % (n = 194/236) of the tested students. None of these students had detectable HBsAg. Conclusion: This study showed anti-HBs level weaned after almost two decades of vaccination. Therefore, an alternative new testing algorithm such as the administration booster dose of hepatitis B vaccination can be considered in order to ensure that the new students are protected against potential exposure to hepatitis B during their clinical practices. International Journal of Human and Health Sciences Vol. 03 No. 04 October’19 Page : 245-248